Criticism of the Effectiveness of Pretrial in Protecting Human Rights Under the Criminal Code - Agustianti Tangahu (SEAN Institute, 2025)
Pretrial is a crucial mechanism in Indonesia's judicial system to protect human rights from potential abuses of authority and procedural errors during legal proceedings. However, its implementation in the Criminal Procedure Code (KUHAP) still raises criticism regarding its effectiveness in ensuring optimal human rights protection. This study aims to analyze the effectiveness of pretrial as an instrument for human rights protection based on the Criminal Code, as well as identify structural and practical weaknesses in its implementation. Using normative legal research methods with a descriptive-analytical approach. Data were obtained through a literature study of primary legal sources (KUHAP) and secondary (journals, pretrial rulings), as well as a critical analysis of relevant law enforcement practices. Pretrial plays a significant role in overseeing the legality of detention, search, and confiscation, as well as providing room for correction of procedural violations. However, there are fundamental weaknesses, such as the limited authority of pretrial judges to assess the legality of searches/seizures, reliance on the independence of judicial institutions, and low public legal awareness in accessing this mechanism